Edupreneur Kesehatan Digital : Inovasi Siswa dalam Promosi Kesehatan dan Kewirausahaan Sekolah - Suci Safwa Salsabila; Nur Akifa Sartika Putri; Aulia Apriliani (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Digital Health Edupreneurship is a concept of student empowerment that integrates health education, digital technology, and entrepreneurial skills. Through this approach, students are not only passive recipients of information but also active creators of digital innovations,such as mobile apps, social media content, educational videos, and online platforms,designed to promote healthy behaviors within schools and the broader community. The main objective of this initiative is to explore and analyze how student innovation in digital health can serve as an effective tool for health promotion while simultaneously fostering entrepreneurial spirit among students. The method used in this program involves lectures and interactive demonstrations. The activity was carried out in three stages: planning and preparation, implementation and process, and finally evaluation and monitoring. Throughout the implementation phase, students were guided to form innovation groups, develop relevant digital content, and collaboratively present their ideas. These activities not only encouraged creativity but also enhanced student engagement in real-world applications of both health promotion and entrepreneurship.The results revealed a significant improvement in students’ knowledge. Prior to the program, only 25.9% of students were categorized as having good knowledge. After the digital health edupreneurship session, this number increased to 88.9%. These findings indicate that the Digital Health Edupreneurship approach is effective in improving health literacy and cultivating student creativity and entrepreneurial mindset in a practical and collaborative learning environment